Interruption of the limitation of action and sanction. Analysis of statements given to the prosecutor and the conditions for its application (Legal journal - Research in Legal and Social Sciences, 2020)
The limitation is one of the means for the expiry of criminal proceedings according to the scopes established in the Penal Code. This article verifies the conditions for the interruption and its effects, specially, in reference to the defendant's citation to hearing made by the Public Ministry, as an investigative proceeding, and to the defendant's citation as an investigative proceeding made by the jurisdictional competent authority. It clarifies whether or not the citation to hearing made by the prosecutor, before the charging, causes the interruptive effect foreseen in the legislation, both for the action and sanction, furthermore, this paper also determines the effects of the citation made after the charging, exposing doctrinal criteria and decisions of those who support these contradictory positions. The present investigation is descriptive, since it describes and analyses the penal code's articles related to the theme, as well as the their application.
Keywords: limitation; interruption; citation; hearing; investigative proceeding; jurisdictional act